Multidrug punch cards in primary care: a mixed methods study on patients' preferences and impact on adherence - Boeni, Fabienne; Hersberger, Kurt E.; Arnet, Isabelle (Frontiers in Pharmacology, 2014)
Background: Multidrug punch cards are frame cards with 28 plastic cavities filled with a patient’s oral solid medication. They are used in primary care to facilitate medication management and to enhance adherence. Main criticism concerned handling difficulties and fading knowledge about medication of patients using them. This study aimed at exploring daily use, preferences and adherence of primary care patients using multidrug punch cards. Methods: Community pharmacies in Switzerland recruited primary care patients using multidrug punch cards. A mixed methods approach was applied with quantitative interviews performed by telephone and qualitative interviews face-to-face. Results: Of 149 eligible patients from 21 community pharmacies, 22 participated 2011 in the quantitative and 11 participated 2013/14 in the qualitative interview. Patients were very satisfied with the multidrug punch cards and stated increased medication safety. All considered adherence as very important. Self-reported adherence was 10 (median) on a visual analogue scale (0 = no intake, 10 = perfect adherence). The absence of package inserts and predefined handling difficulties e.g., tablets spiking at removal were not perceived as problems. Conclusions: Patients are satisfied with the multidrug punch cards, feel safe, mostly have no handling problems and adhere to their treatment. Trust in health-care professionals and patients’ experiences emerged as key variables for initiating multidrug punch card use and for medication adherence. This mixed methods study invalidates previous concerns about disadvantages of multidrug punch cards. Health-care professionals should actively recommend them for primary care patients with polypharmacy and poor adherence.